The impacts of refugee repatriation on receiving communities - Ruiz-Olaya, I; Vargas-Silva, C (Oxford University Press, 2020)
Using longitudinal data from Burundi, we explore the consequences of refugee repatriation for stayee households in a context in which returnees faced restrictions on economic activities and mobility while abroad. We use geographical features of the receiving communities, including altitude and distance to the border, for identification. We find that a 1 percentage point increase in the local share of the population accounted for by returnees leads to a reduction in the livestock of stayee households which is equivalent to 1 fowl per adult member or a 5% with respect to the mean. A higher share of returnees in a community also leads to less land access, lower subjective well-being and higher food insecurity for stayees. The negative effects on subjective well-being and food security disappear over the rounds of the survey (5 years), likely as a consequence of stayee households adjusting their economic activities in response to the presence of returnees.